The Income Tax of Breadwinner Wives in Indonesia: Law and Economics Approach - Johan, Arvie (Universitas Airlangga, 2024)
The inequality of employment opportunities between women and men in Indonesia is quite worrying: the low employment of women, the low income of women, the minimum number of women who reach the top of their careers, and the majority of women are positioned as housekeepers. Inequality attracts the issue of income tax of breadwinner wives. The income tax regulations already accommodate equality between men and women, but various groups including the Indonesia Minister of Finance consider this regulation to be insufficient. This article analyzes imposition of income tax on women in relation to the discrepancies of breadwinner roles between women and men. This article applies a law and economics approach, focusing on the importance of efficiency in order to maintain gender-neutral equality. The result, is that the approach in the context of income tax is applicable in Indonesia by introducing the concept of imputed income based on provincial minimum wage, and by applying lower tax income rate for breadwinner wives. The introduction of imputed income based on provincial minimum wage requires regulatory support from the national social security system in order to include non-wage workers. This article concludes that the key to solving inequality problem in income tax regulation is the parity in price or value between husbands and wives, either in the role of homemaker or breadwinner. As suggestion, imputed income must be complemented with the imposition of lower rates on the income of working wives, as the roles of husbands as breadwinner and wives as breadwinner are in close substitution. Consequently, the bargaining power of wives for the role of breadwinners is stronger.